A COMPREHENSIVE ANALYSIS OF THE IMPACT OF VAPING (ELECTRONIC CIGARETTE USE) ON THE EDUCATIONAL PROCESS, COGNITIVE FUNCTIONS, AND ACADEMIC PERFORMANCE OF UNIVERSITY STUDENTS - Dilbakhor Umaralievna Temirova; Shokhrukhbek Oybek ogly Rakhimov (Bright Mind Publishing, 2026)
This article presents a comprehensive analysis of the impact of electronic cigarette use (vaping) among students on the educational process, cognitive functions, and academic performance. The aim of the study is to identify the relationship between vaping and students’ attention, memory, academic motivation, psycho-emotional state, and learning outcomes. The research methodology is based on the analysis of scientific literature, sociological surveys, comparative methods, and analytical approaches. The results indicate that regular vaping is associated with decreased concentration, increased fatigue, heightened anxiety levels, and impaired cognitive performance. Students who use electronic cigarettes demonstrate lower academic motivation, higher absenteeism rates, and reduced academic achievement compared to non-vaping peers. The findings are consistent with the author’s previous research, which identified a relationship between students’ health indicators and behavioral risk factors. The study emphasizes the importance of implementing comprehensive preventive strategies in higher education institutions, including health education programs, psychological support, and digital health interventions aimed at reducing vaping prevalence and promoting healthy lifestyle behaviors. The conclusions of the study may be used to improve student health protection policies and enhance the effectiveness of the educational process.
Keywords: Vaping, electronic cigarettes, students, educational process, cognitive functions, academic performance, prevention